Digital libraries and archives : 13th Italian Research Conference on Digital Libraries, IRCDL 2017, Modena, Italy, January 26-27, 2017, Revised selected papers /: 13th Italian Research Conference on Digital Libraries, IRCDL 2017, Modena, Italy, January 26-27, 2017, Revised selected papers. (2017) - Unknown
No abstract available